E0665 Clinical feature and follow-up results of 60 patients with pulmonary artery hypertension. (17th November 2010) - Sun, Yuemin; Zhao, Guoyan; Yang, Zhenwen
Abstract : Objective: To review the clinical feature of pulmonary artery hypertension (PAH) and analyse the results of following up. Methods: Clinical feature of 60 PAH patients who was diagnosed as PAH from Dec 2007 to Dec 2009 were reviewed retrospectively and those patients were followed up. Results: Six patients (three patients were CTD) died and six patients lost contact during following up. Those patients were divided into two groups based on pathogeny, Pulmonary Arterial Hypertension Associated With Connective Tissue Diseases (PAH-CTD) group (n=23) and the Pulmonary Arterial Hypertension Associated With Non-Connective Tissue Diseases PAH-Non-CTD) group (n=25). The former patient's condition obvious more critical than the latter and 20 patients using PAH targeted drug. In the course of follow-up, the condition had relieved somewhat in the two group patients, but the former still serious than the latter. Conclusion: Many complicated reasons can lead to PAH. The patients of Pulmonary Arterial Hypertension Associated With Connective Tissue Diseases had high morbidity and unfavourable prognosis. It is beneficial for PAH-CTD patient's administrated with targeted drug treatment and pay attention to follow-up visit.